Efforts to Form a Good Family Through Family Counseling and Psychotherapy - Elvia Kurniawati; Mudjiran; Yeni Karneli (Journal Of Psychology, Counseling And Education, 2024)
This article discusses the importance of family counseling and psychotherapy in dealing with various problems that often occur in the family unit. Family counseling and psychotherapy are therapeutic approaches that aim to improve relationships and communication between family members and help overcome emotional and psychological problems that affect the family as a whole. Through various methods and techniques, family therapy can provide effective solutions to various conflicts, improve mental and emotional well-being, and strengthen family bonds. This article will also outline some of the approaches commonly used in family therapy, including systemic therapy, structural therapy, and strategic therapy. The methodology used in this study is a literature review with data collection from various reading sources. The results of this study are Counseling adolescents and parents requires an in-depth understanding of developmental challenges in adolescents and the role of counselors in providing appropriate assistance and support.